Overweight and Helicobacter pylori infection: a correlation in metabolic dysfunction-associated fatty liver disease - Xu Chen; Jiayue Fu; Jiayue Fu; Kejia Jin; Kejia Jin; Zixuan Yang; Zixuan Yang; Yidan Qian; Yidan Qian; Kehan Mei; Yihan Wang; Jialei Min; et al. (Frontiers in Cellular and Infection Microbiology)
BackgroundMetabolic dysfunction-associated fatty liver disease (MAFLD) has recently replaced nonalcoholic fatty liver disease (NAFLD) as a term that more accurately describes its pathogenesis. Helicobacter pylori (H. pylori), a bacterium that infects over half the world’s population, has been increasingly linked to various extragastric diseases. However, the impact of H. pylori on MAFLD in the Chinese population remains unexplored.MethodsA retrospective cross-sectional study was conducted, encompassing 5619 participants from the First Affiliated Hospital of Wenzhou Medical University, spanning from April 2016 to August 2017. Detection of H. pylori was achieved through the 13C urea breath test or gastric biopsies with histochemical staining. Fatty liver was primarily diagnosed via ultrasound and assessed alongside metabolic indicators to confirm MAFLD. Logistic regression was utilized to evaluate the association between H. pylori and MAFLD.ResultsNo significant correlation between H. pylori infection and MAFLD was found in the overall population through either univariate (OR=1.136, 95%CI 0.995-1.297, p=0.059) or multivariate logistic regression analysis (OR=1.036, 95%CI 0.877-1.224, p=0.675). However, subgroup analysis revealed a significant association in overweight individuals (BMI ≥ 23 kg/m2) within the MAFLD group (51.2% vs. 35.5%, p=0.002), a pattern not observed in the non-MAFLD group (47.7% vs. 45.4%, p=0.126). This association persisted after adjusting for confounders (OR=1.957, 95%CI 1.176-3.256, p=0.010).ConclusionOverweight individuals with MAFLD have a higher prevalence of H. pylori infection than their lean counterparts. This suggests a detrimental cycle between overweight status and H. pylori infection in MAFLD patients, potentially exacerbating metabolic deterioration. Therefore, eradication of H. pylori infection may have positive implications for reducing the incidence rate of overweight MAFLD.